Recombinant human HSP60 produced in ClearColi™ BL21(DE3) does not activate the NFκB pathway. Issue 1 (May 2015) - Planesse, Cynthia; Nativel, Brice; Iwema, Thomas; Gasque, Philippe; Robert-Da Silva, Christine; Viranaïcken, Wildriss
Graphical abstract